2018
DOI: 10.3847/1538-4365/aaa00a
|View full text |Cite
|
Sign up to set email alerts
|

The WISE AGN Catalog

Abstract: We present two large catalogs of active galactic nucleus (AGN) candidates identified across 30,093 deg 2 of extragalactic sky from the Wide-field Infrared Survey Explorer's AllWISE Data Release. Both catalogs are selected purely using the Wide-field Infrared Survey Explorer (WISE) W1and W2 bands. The R90 catalog consists of 4,543,530 AGN candidates with 90% reliability, while the C75 catalog consists of 20,907,127 AGN candidates with 75% completeness. These reliability and completeness figures were determined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
285
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(291 citation statements)
references
References 84 publications
6
285
0
Order By: Relevance
“…Since 2010 January, the polar-orbit WISE satellite has imaged the full sky approximately every six months. Assef et al (2018a) presents a catalog of WISEselected AGNs across most of the extragalactic sky, with 4.5 million AGN candidates identified at 90% reliability, and nearly 21 million AGN candidates identified at 75% completeness (but 51% reliability). As part of that work, Assef et al (2018a) discuss the subset of 687 high-reliability AGNs identified as highly mid-IR variable during the first year of WISEobservations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2010 January, the polar-orbit WISE satellite has imaged the full sky approximately every six months. Assef et al (2018a) presents a catalog of WISEselected AGNs across most of the extragalactic sky, with 4.5 million AGN candidates identified at 90% reliability, and nearly 21 million AGN candidates identified at 75% completeness (but 51% reliability). As part of that work, Assef et al (2018a) discuss the subset of 687 high-reliability AGNs identified as highly mid-IR variable during the first year of WISEobservations.…”
Section: Introductionmentioning
confidence: 99%
“…Assef et al (2018a) presents a catalog of WISEselected AGNs across most of the extragalactic sky, with 4.5 million AGN candidates identified at 90% reliability, and nearly 21 million AGN candidates identified at 75% completeness (but 51% reliability). As part of that work, Assef et al (2018a) discuss the subset of 687 high-reliability AGNs identified as highly mid-IR variable during the first year of WISEobservations. Considering the subset of these sources not detected at radio energies, so as to avoid blazars, they present one quasar, WISEAJ142846.71+172353.1, whose broad Hα emission has disappeared between an SDSS spectrum obtained in 2008 and a Palomar spectrum obtained in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The completion of the Wide-field Infrared Survey Explorer (WISE; Wright et al 2010) survey of the full sky has allowed us to make dramatic progress in statistical studies of AGNs (e.g., Mor & Trakhtenbrot 2011;Donoso et al 2012;Edelson & Malkan 2012;Eisenhardt et al 2012;Ichikawa et al 2012;Mateos et al 2012;Plotkin et al 2012;Sajina et al 2012;Stern et al 2012;Assef et al 2013;Geach et al 2013;DiPompeo et al 2014DiPompeo et al , 2015DiPompeo et al , 2016DiPompeo et al , 2017Assef et al 2015Assef et al , 2017Secrest et al 2015). In particular, WISE enables us to detect and characterize hundreds of thousands of obscured quasars, increasing the sizes of obscured quasar samples by two orders of magnitude and allowing the first large statistical studies of their properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the W1-W2 is little affected by extinction, in particular at low redshifts (e.g., Stern et al 2012), making W1-W2 based AGN selection a formidable tool to select highly obscured and even CT AGN. Here, we will use the most recent and refined selection criterion introduced in Assef et al (2018), namely one that was designed to have 90% reliability in selecting AGN (hereafter R90):…”
Section: Identification Of Agn By Mir Colourmentioning
confidence: 99%